Cervical intradural extramedullary chaotic lipoma in an elderly patient: A rare case report - Anurup Saha; Sibaji Dasgupta (Asian Journal of Medical Sciences, 2023)
Intradural spinal lipoma (ISL) prevalent in children and young adults usually presents with spastic progressive quadriparesis, sensory disturbances, and gait abnormalities. Chaotic lipomas named due to their haphazard distribution are an extremely rare variant of ISL present at the dorsal root entry zone. We describe a case of chaotic spinal lipoma and elucidate the challenges faced in the management of this entity.